Change Detection of Landuse-landcover in and around Cox’s Bazar-Teknaf Coastal Area of Bangladesh Using Satellite Images (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
The prime objective of this study is to detect changes of the biophysical resources (or landuse-landocver) of the Cox’s Bazar-Teknaf area from 1999 to 2015 using Landsat TM/ETM+/OLI sensors images after applying classifications and indices approaches. The normalized differential vegetation index (NDVI) result showed that water bodies reduced by about 20% of the study area from 1999 to 2015. Bared land or beach decreased by 6% from 1999 to 2005 and then increasing trend is observed in this study from 2005 to 2015. Mixed land was more or less an increasing trend in this study area. Vegetation cover increased from 1999 to 2005 and then suddenly decreased a lot from 2009 to 2015. The declining trend of water bodies is mostly in the northern part of the study area, which is mostly shallow area where shrimp or salt farms exist. The result of normalized differential water index (NDWI) showed that the water bodies decreased from 1999 to 2015 about 10% of the study area. Land area was increased from 1999 to 2005 and then increased a little from 2005 to 2009 and afterward it decreased. The normalized differential salinity index (NDSI) result shows that the area of non-saline zone increased from 1999 to 2015. Low saline zones reduced from 1999 to 2005 but it increased after 2005 due to absence of high and medium salinity signature from NDSI value. The low saline zone is mostly in the northern side of Cox’s Bazar where shrimp farms or salt bed exist. In unsupervised thematic maps, the water bodies increased in this region from 1999 to 2009 and then declined again. The declining trend of water bodies indicates the erosion activities from 1999 to 2009. The fallow lands including beach also decreased from 2005 to 2015, indicates more agricultural activities including fisheries, salt production in this study area. On the other hand, the vegetated region decreased but settlements area including vegetation increased in this area. In supervised thematic map, the result showed that the shrimp cultivation and salt bed increased in this region from 1999 to 2015 and agricultural land has decreasing trend. On the other hand, the vegetated region was ups and down trend from 1999 to 2009. The study indicates that the Landsat images are quite efficient to map biophysical resources of the study area with various techniques.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(1), 2019, P 1-9